Thematic evolution of information literacy from core competency to digital strategy (2014-2024) - Rully Khairul Anwar; Yunus Winoto; Widia Lestari (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. The lack of comprehensive and up-to-date bibliometric studies may lead to gaps in understanding global library information literacy trends. This study aims to trace these trends for 2014–2024, identify key research topics, and map the most productive authors and countries. Research Methods. This study used bibliometric analysis of 951 scientific articles indexed by Scopus. Data Analysis. Data was extracted and analyzed using Biblioshiny software. Results. The findings reveal a significant thematic shift towards digital transformation, with 'digital literacy' and 'digital libraries' emerging as motor themes that drive the research field. The United States is identified as the most productive country, while Goh Dion Hoe-Lian and Guo Yan Ru are the most influential authors. Conclusion. This study concludes that information literacy has evolved from a foundational skill into a strategic component integrated with digital library services. The novelty lies in its comprehensive 11-year mapping, which quantitatively demonstrates the field's structural evolution and identifies the core, niche, and emerging research clusters, providing a definitive map of the intellectual landscape.